2017
DOI: 10.5114/dr.2017.71218
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of liver function in patients with psoriasis vulgaris

Abstract: Introduction. Patients with psoriasis develop nonalcoholic fatty liver disease more often than healthy subjects. Objective. To estimate the level of basic parameters of liver function, compare these values between groups of patients with psoriasis and healthy individuals, and refer these values to selected risk factors of developing atherosclerosis. Material and methods. A case-control study in the dermatology department included 66 patients with psoriasis and 30 healthy volunteers. The two groups were compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Our study also showed that there was an increase in neutrophil/lymphocyte ratio and platelet/lymphocyte ratio in psoriasis patients compared with controls, and this was consistent with another study performed to estimate these parameters in psoriasis patients, and they found that they were all significantly higher in moderate to severe psoriasis patients [25]. Also, there was no significant variation among the two groups concerning AST and ALT; this was consistent with another study that found the activity and concentration of liver function markers (ALT and AST) did not differ significantly between healthy individuals and cases with psoriasis [26]. Our study showed that there was no significant distinction amongst the two groups concerning serum creatinine levels, and this is consistent with another study that found the median levels of serum creatinine…”
Section: Mapkssupporting
confidence: 89%
“…Our study also showed that there was an increase in neutrophil/lymphocyte ratio and platelet/lymphocyte ratio in psoriasis patients compared with controls, and this was consistent with another study performed to estimate these parameters in psoriasis patients, and they found that they were all significantly higher in moderate to severe psoriasis patients [25]. Also, there was no significant variation among the two groups concerning AST and ALT; this was consistent with another study that found the activity and concentration of liver function markers (ALT and AST) did not differ significantly between healthy individuals and cases with psoriasis [26]. Our study showed that there was no significant distinction amongst the two groups concerning serum creatinine levels, and this is consistent with another study that found the median levels of serum creatinine…”
Section: Mapkssupporting
confidence: 89%